2020
DOI: 10.3390/s20133672
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Upper Limb Joint Kinetics of a Golf Swing with Measured Internal Grip Force

Abstract: The biomechanics of a golf swing have been of interest to golfers, instructors, and biomechanists. In addition to the complexity of the three-dimensional (3D) dynamics of multi-segments of body, the closed-chain body posture as a result of both hands holding a club together makes it difficult to fully analyze the 3D kinetics of a golf swing. To identify the hand-grip joint force and torque applied by each hand, we directly measured the 3D internal grip force of nine registered professional golfers using an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We used a Simscape model to simulate the torque-based control approach in which the model consists of a DC motor model, torque control law and forearm inertia model (Figure 5). The arm torque was calculated according to (9). It was then fed to the DC motor model as a torque feedback signal in which the error signal between the motor and arm torque is used as an actuating signal for the DC motor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a Simscape model to simulate the torque-based control approach in which the model consists of a DC motor model, torque control law and forearm inertia model (Figure 5). The arm torque was calculated according to (9). It was then fed to the DC motor model as a torque feedback signal in which the error signal between the motor and arm torque is used as an actuating signal for the DC motor.…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing interest in developing an upper limb exoskeleton for physiotherapy, ergonomic work environment, and athletic ability assessment. [5][6][7][8][9] Many studies have been published on estimating arm torques, such as Li et al 10 , Hwang and Jeon, 11 and Makhni et al 12 In Li et al, 10 the authors proposed estimating elbow joint torque using myoelectrical feedback signals and inertial measurement units (IMUs) in which these measurements are amplified and sent to the OpenSim-Matlab system for actuating and controlling an exoskeleton joint. Mikołajczyk et al 4 suggested using joint torque sensor and limb dynamics to estimate muscular torque and implemented their method on a wheelchair lower limb exoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in joint torque 3D dynamic human model [76][77][78] Reduction in muscle effort Musculoskeletal human model [79,80] Hypothesis of quasi-static equilibrium Dynamic human model [81] Reduction in joint fatigue 2D three-compartment controller fatigue model [82] Simple dynamic models are usually represented by rigid elements and joints with different degrees of freedom without spring or damper properties. An evaluation of these dynamic models is conducted via an inverse kinematic analysis.…”
Section: Optimization Criterium Digital Human Models Relevant Studiesmentioning
confidence: 99%
“…In such cases, the main input condition is the impact of an external force on the human body. The main application domains of the studies investigated are healthcare-especially for patient monitoring- [13,22,35,39,[46][47][48]61,64,71], sleep research [45,49,[91][92][93], sports science [37,76,94], product [84] and automotive design [34,87,88] and the sub-domains of ergonomics-industrial ergonomics [12,50,77,80,82,86,89,95,96], gait analyses [43,51,65,85,97] and sitting ergonomics [14,16,21,44,54,69,72,[98][99][100][101]. The context of the application scenarios also influences the estimation methods th...…”
Section: Application Scenariosmentioning
confidence: 99%
“…Maintenance activities related to golf courses have also been described, by taking advantage of static wireless sensor networks combined with remote sensing data in order to monitor environmental parameters such as soil moisture [ 16 ]. Table 1 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] summarizes some relevant contributions related to golf sport. It presents works focused on improving the movements of the golf player, specifically the swing motion.…”
Section: Introductionmentioning
confidence: 99%